Clinical features and early treatment response of central nervous system involvement in childhood acute lymphoblastic leukemia. Issue 8 (12th February 2014) - Levinsen, Mette; Taskinen, Mervi; Abrahamsson, Jonas; Forestier, Erik; Frandsen, Thomas L.; Harila‐Saari, Arja; Heyman, Mats; Jonsson, Olafur G.; Lähteenmäki, Päivi M.; Lausen, Birgitte; Vaitkevičienė, Goda; Åsberg, Ann; et al.
<x xml:space="preserve">Abstract</x> Background Central nervous system (CNS) involvement in childhood acute lymphoblastic leukemia (ALL) remains a therapeutic challenge. Procedure To explore leukemia characteristics of patients with CNS involvement at ALL diagnosis, we analyzed clinical features and early treatment response of 744 patients on Nordic‐Baltic trials. CNS status was classified as CNS1 (no CSF blasts), CNS2 (<5 leukocytes/µl CSF with blasts), CNS3 (≥5 leukocytes/µl with blasts or signs of CNS involvement), TLP+ (traumatic lumbar puncture with blasts), and TLP− (TLP with no blasts). Results Patients with CNS involvement had higher leukocyte count compared with patients with CNS1 (P < 0.002). Patients with CNS3 more often had T‐ALL (P < 0.001) and t(9;22)(q34;q11)[BCR‐ABL1] (P < 0.004) compared with patients with CNS1. Among patients with CNS involvement headache (17%) and vomiting (14%) were most common symptoms. Symptoms or clinical findings were present among 27 of 54 patients with CNS3 versus only 7 of 39 patients with CNS2 and 15 of 75 patients with TLP+ (P < 0.001). The majority of patients with CNS involvement received additional induction therapy. The post induction bone marrow residual disease level did not differ between patients with CNS involvement and patients with CNS1 (P > 0.15). The 12‐year event‐free survival for patients with leukemic mass on neuroimaging did not differ from patients with negative or no scan (0.50 vs. 0.60; P = 0.7) or between patients with symptoms or signs suggestive of CNS leukemia and patients without such characteristics (0.50 vs. 0.61; P = 0.2). Conclusion CNS involvement at diagnosis is associated with adverse prognostic features but does not indicate a less chemosensitive leukemia. Pediatr Blood Cancer 2014; 61:1416–1421. © 2014 Wiley Periodicals, Inc.